Beggar Thy Neighbor : A History of Usury and Debt - Geisst, Charles R. (Book collections on Project MUSE., 2013)
In this book, a financial historian tracks the changing perceptions of usury and debt from the time of Cicero to the financial crises of the early twenty-first century. This comprehensive economic history looks at humanity's attempts to curb the abuse of debt while reaping the benefits of credit. The book examines the major debt revolutions of the past, demonstrating that extensive leverage and debt were behind most financial market crashes from the Renaissance to the present. The author argues that usury prohibitions, as part of the natural law tradition in Western and Islamic societies, continue to play a key role in banking regulation despite modern advances in finance. From the Roman Empire to the Dodd-Frank financial reforms, usury ceilings still occupy a central place in notions of free markets and economic justice.